The Study of Hydrothermal Carbonization and Activation Factors' Effect on Mesoporous Activated Carbon Production From Sargassum sp. Using a Multilevel Factorial Design - Prakoso, Tirto; Rustamaji, Heri; Yonathan, Daniel; Devianto, Hary; Widiatmoko, Pramujo; Rizkiana, Jenny; Guan, Guoqing (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2022)
Seaweeds are large-scale multicellular marine algae categorized based on color as Chlorophyceae, Rhodophyceae, and Phaeophyceae. No information has been provided on the conditions affecting the production of mesoporous activated carbon from one member of the described aquatic plants, namely Sargassum sp. Therefore, this study aimed to determine the impact of the main factors and their interactions on Sargassum sp.-derived activated carbon manufactured (SAC) by hydrothermal carbonization and CO2 activation methods. A mathematical approach was employed using a multilevel factorial design with the main factors being the activator type (ZnCl2, CaCl2, & KOH), hydrothermal temperature (200, 225, & 250oC), and activator ratios (2 & 4). Meanwhile, the response variables were yield and BET surface area (SBET) of SAC. Morphological, functional, crystallographic, and porosity characterization was carried out on the samples. The SAC-Ca-200-2 sample had the highest yield, with the value being 26.5 percent of weight. The activators having the highest specific surface area (SBET) were SAC-Zn-250-4, SAC-Ca-225-2, and SAC-K-250-2, with 1552, 1368, and 1799 m2/g, respectively. The pore size distribution in SAC products ranged from 2.16 to 10 nm in diameter. The analysis conducted indicated the activator type and interaction with its ratio substantially impacted the SAC yield value; besides, only the activator type affects the formation of high surface area pores.